Maintenance with daratumumab or observation following treatment with bortezomib, thalidomide, and dexamethasone with or without daratumumab and autologous stem-cell transplant in patients with newly diagnosed multiple myeloma (CASSIOPEIA): an open-label, randomised, phase 3 trial. Issue 10 (October 2021) - Moreau, Philippe; Hulin, Cyrille; Perrot, Aurore; Arnulf, Bertrand; Belhadj, Karim; Benboubker, Lotfi; Béné, Marie C; Zweegman, Sonja; Caillon, Hélène; Caillot, Denis; Corre, Jill; Delforge, Michel; et al.
Summary: Background: CASSIOPEIA part 1 showed superior depth of response and significantly improved progression-free survival with daratumumab, bortezomib, thalidomide, and dexamethasone (D-VTd) versus bortezomib, thalidomide, and dexamethasone (VTd) as induction and consolidation in patients with autologous stem-cell transplant (ASCT)-eligible newly diagnosed multiple myeloma. In part 2, we compared daratumumab maintenance versus observation only. Methods: CASSIOPEIA is a two-part, open-label, randomised, phase 3 trial of patients aged 18–65 years with newly diagnosed multiple myeloma and Eastern Cooperative Oncology Group performance status 0–2, done in 111 European academic and community practice centres. In part 1, patients were randomly assigned (1:1) to induction and consolidation with D-VTd or VTd. Patients still on study who had a partial response or better were randomly assigned (1:1) by an interactive web-response system to daratumumab 16 mg/kg intravenously every 8 weeks (a reduced frequency compared with standard daratumumab long-term dosing) or observation only for up to 2 years. Stratification factors were induction treatment and depth of response in part 1. The part 2 primary endpoint was progression-free survival from second randomisation. This preplanned interim analysis of progression-free survival was done after 281 events and shall be considered the primary analysis of progression-free survival. Sponsor personnel and designees who were involved in the analysis were masked to treatment group until the independent data monitoring committee recommended that the preplanned interim analysis be considered the main analysis of progression-free survival in part 2. Otherwise, treatment assignments were unmasked. The interaction between induction and consolidation and maintenance was tested at a two-sided significance level of 0·05 by a stratified Cox regression model that included the interaction term between maintenance treatment and induction and consolidation treatment. Efficacy analyses were done in the maintenance-specific intention-to-treat population, which comprised all patients who underwent second randomisation. Safety was analysed in all patients in the daratumumab group who received at least one dose and all patients randomly assigned to observation only. This trial is registered with ClinicalTrials.gov, NCT02541383 . Long-term follow-up is ongoing and the trial is closed to new participants. Findings: Between May 30, 2016, and June 18, 2018, 886 patients (458 [84%] of 543 in the D-VTd group and 428 [79%] of 542 in the VTd group) were randomly assigned to daratumumab maintenance (n=442) or observation only (n=444). At a median follow-up of 35·4 months (IQR 30·2–39·9) from second randomisation, median progression-free survival was not reached (95% CI not evaluable [NE]–NE) with daratumumab versus 46·7 months (40·0–NE) with observation only (hazard ratio 0·53, 95% CI 0·42–0·68, p<0·0001). A prespecified analysis of progression-free survival results showed a significant interaction between maintenance and induction and consolidation therapy (p<0·0001). The most common grade 3 or 4 adverse events were lymphopenia (16 [4%] of 440 patients in the daratumumab group vs eight [2%] of 444 patients in the observation-only group), hypertension (13 [3%] vs seven [2%]), and neutropenia (nine [2%] vs ten [2%]). Serious adverse events occurred in 100 (23%) patients in the daratumumab group and 84 (19%) patients in the observation-only group. In the daratumumab group, two adverse events led to death (septic shock and natural killer-cell lymphoblastic lymphoma); both were related to treatment. Interpretation: Daratumumab maintenance every 8 weeks for 2 years significantly reduced the risk of disease progression or death compared with observation only. Longer follow-up and other ongoing studies will shed further light on the optimal daratumumab-containing post-ASCT maintenance treatment strategy. Funding: Janssen Research & Development, the Intergroupe Francophone du Myélome, and the Dutch-Belgian Cooperative Trial Group for Hematology Oncology.